INVESTIGATION OF THE ABRASION RESISTANCE OF THE QUARTZITIC NATURAL AGGREGATE FOR DIFFERENT TEST PARAMETERS - Tunc, Esra Tugrul (E-Journal of New World Sciences Academy, 2018)
Turkey has many types of aggregates that have different chemical and physical properties. Waste aggregates or low-cost aggregates must be evaluated in the industry to benefit the environment. Turkey has large water reserves. Therefore, the usability of natural aggregates, created by the sweeping of water in places like river beds, lakes, and coasts, in industrial areas such as construction and metallurgy should be investigated. Because these aggregates have a quartzitic characteristic, it is also believed that their strength will be high. In this study investigates the abrasion resistance of natural aggregates with quartzite characteristics obtained from river beds in the Mediterranean Region. This study aims to investigate the usability of these natural aggregates in concrete. For the usability of these quartzitic natural aggregates in concrete, it has been investigated whether they have the appropriate abrasion value conforming the relevant Turkish Standard. Thus, it is aimed to provide both an environmentally friendly production and economic gain. The present study was carried out experimentally using the Los Angeles test device for different test parameters. From this study, it has been concluded that these natural aggregates can be used for the production of concrete which has sufficient strength especially in terms of abrasion resistance. The abrasion resistance of the aforementioned aggregates was compared with the abrasion resistance of aggregates with different properties used in previous studies.

Turkey has many types of aggregates that have different chemical and physical properties. Waste aggregates or low-cost aggregates must be evaluated in the industry to benefit the environment. Turkey has large water reserves. Therefore, the usability of natural aggregates, created by the sweeping of water in places like river beds, lakes, and coasts, in industrial areas such as construction and metallurgy should be investigated. Because these aggregates have a quartzitic characteristic, it is also believed that their strength will be high. In this study investigates the abrasion resistance of natural aggregates with quartzite characteristics obtained from river beds in the Mediterranean Region. This study aims to investigate the usability ofthese natural aggregates in concrete. For the usability of these quartzitic natural aggregates in concrete, it has been investigated whether they have the appropriate abrasion value conforming the relevant Turkish Standard. Thus, it is aimed to provide both an environmentally friendly production and economic gain. The present study was carried out experimentally using the Los Angeles test device for different test parameters. From this study, it has been concluded that these natural aggregates can be used for the production of concrete which has sufficient strength especially in terms of abrasion resistance. The abrasion resistance of the aforementioned aggregates was compared with the abrasion resistance of aggregates with different properties used in previous studies.
INVESTIGATION OF THE ABRASION RESISTANCE OF THE QUARTZITIC NATURAL AGGREGATE FOR DIFFERENT TEST PARAMETERS